2017
DOI: 10.1177/2325967117724415
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Patient Selection of an Orthopaedic Sports Medicine Physician

Abstract: Background:The rise in consumer-centric health insurance plans has increased the importance of the patient in choosing a provider. There is a paucity of studies that examine how patients select an orthopaedic sports medicine physician.Purpose:To evaluate factors that patients consider when choosing an orthopaedic sports medicine physician.Study Design:Case series; Level of evidence, 4.Methods:A total of 1077 patients who sought treatment by 3 sports medicine physicians were administered an anonymous questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
3
28
1
Order By: Relevance
“…Our results are useful for orthopaedic sports medicine physicians seeking to balance efficiency and patient satisfaction as health care becomes increasingly value driven and consumer focused. Although previous studies have noted the physician's training background and credentials to be among the most important selection criteria considered by patients, [9][10][11] none have examined the midlevel provider's training background as a selection criterion. Our patients considered the midlevel provider's credentials when initially choosing a new sports medicine physician ( Figure 2), and most patients perceived no difference in the training levels of PAs and NPs (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are useful for orthopaedic sports medicine physicians seeking to balance efficiency and patient satisfaction as health care becomes increasingly value driven and consumer focused. Although previous studies have noted the physician's training background and credentials to be among the most important selection criteria considered by patients, [9][10][11] none have examined the midlevel provider's training background as a selection criterion. Our patients considered the midlevel provider's credentials when initially choosing a new sports medicine physician ( Figure 2), and most patients perceived no difference in the training levels of PAs and NPs (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…23,26,28-31 One study measured distance as travel time. 36 In six articles there was no calculation of actual distances at all, 24,25,33,34,37,38 but the role of distance was assessed and hence a general willingness to bypass the nearest provider could be assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Especially patients without a medical background might not be able to rate quality themselves but rather refer to other sources. The most common alternatives are to rely on friends’ or families’ experiences or recommendations 36-38 or using the internet. In the latter, it was shown that the way information is presented determines how it is understood and used.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have found the surgeon’s credentials to be among patients’ top selection criteria, none investigated the physician extender’s credentials as a selection factor. 7-9 Our data suggest inclusion of midlevel providers in marketing initiatives such as practice websites may be worthwhile as most patients consider the physician extender’s credentials and training when choosing a new hand surgeon (Figure 2). Nearly one-third of our cohort perceived PAs as more highly trained than NPs (Figure 1).…”
Section: Discussionmentioning
confidence: 97%